The infinite sea - Yancey, Richard (New York, N.Y. : Speak, 2015)
"Cassie Sullivan and her companions lived through the Others' four waves of destruction. Now, with the human race nearly exterminated and the 5th Wave rolling across the landscape, they face a choice: brace for winter and hope for Evan Walker's return, or set out in search of other survivors before the enemy closes in"--Provided by publisher.
Young Adult
Keywords: Extraterrestrial beings -- Juvenile fiction; Survival -- Juvenile fiction; Extraterrestrial beings -- Fiction; Survival -- Fiction; War fiction; Science fiction